THE SIGNIFICANCE OF USING INNOVATIONS IN THE TRAINING OF FUTURE PEDAGOGUES - Gʻafforova Dilshoda Amirqulovna; Quziboyeva Samida Solijon qizi (Journals Park Publishing, 2023)
In this article, the innovative professional of future teacher about the unique pedagogical and psychological features of the process of preparation for activit in the field of theory and practice of pedagogical innovation in teacher attention is paid to arousing great interest in scientific work.
Keywords: Pedagogue-future teacher, innovative professional activity, pedagogy practice, competence, creative approach, pedagogical situations.